Fabrication of Cu rich bulk metallic glass composites via solidification method. (February 2014) - Wu, J.; Pan, Y.; Zhang, L.; Pi, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Cu based bulk metallic glasses and composites with tiny crystalline phases embedded in metallic glass matrix have been successfully fabricated by solidification technique in the present work. The formation of crystalline phases and structure inhomogeneity in bulk metallic glasses was characterised. Al is used as the minor alloying element to partly substitute Cu element in 61Cu–34Zr–5Ti. The results show that quarternary 60Cu–34Zr–5Ti–1Al alloy exhibits monoamorphous feature, and 56Cu–34Zr–5Ti–5Al alloy has a few crystalline peaks superimposed on a broad diffraction peak, suggesting that a composite structure forms in certain solidification conditions. To further identify the microstructure of the as cast rod, all samples were characterised by scanning electron microscopy (SEM). Small size phases are found in 2 mm diameter 56Cu–34Zr–5Ti–5Al rod, which has larger plastic deformation. The composition of those crystalline phases is also investigated. All results indicate that the presence of certain phases in metallic matrix benefits the mechanical properties of the as cast bulk metallic glasses.